A Study on Digital Human Resource Management - Its Impact on Employee Turnover - Kanojia, Babita A. (SFIMAR Research Review, 2021)
Here we are going to study Digital Human Resource Management and its impact on the employee’s turnover. In this study we have used cervical method to understand what is the impact of digital Human Resource Management in today’s digital world organisations and businesses and to understand how digital era has helped businesses form an organisation to maintain their Human Resource Management in a developed way. By the cervical method we are also going to know the reasons for employee turnover advantages and disadvantages of digital Human Resource Management and so on. There are many aspects of Human Resource Management, which are covered in this research paper. The present study is based on primary as well as secondary sources of data collection and it will be analyzed with simple statistical tools such as percentage, median and mode.